2012
DOI: 10.1001/archinternmed.2011.1977
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Telephonic Intervention to Improve Medication Regimen Adherence

Abstract: Background Multiple studies demonstrate poor adherence to medications prescribed for chronic illnesses, including osteoporosis, but few interventions have been proven to enhance adherence. We examined the effectiveness of a telephone-based counseling program rooted in motivational interviewing to improve medication adherence for osteoporosis. Methods We conducted a one year randomized controlled clinical trial. Participants were recruited from a large pharmacy benefits program for Medicare beneficiaries. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 25 publications
4
84
2
Order By: Relevance
“…Our meta-analyses found phone-based MI to be superior to usual care among RCTs only among studies reporting a categorical adherence measure, which had a more consistent effect size. The significantly larger effect size of Solomon et al, 32 which reported a continuous measure, created heterogeneity that led to nonsignificant results. Similar limitations occurred in the in-person and group analyses in which Interian et al 19 and Holstad et al 26 also had larger effect sizes.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Our meta-analyses found phone-based MI to be superior to usual care among RCTs only among studies reporting a categorical adherence measure, which had a more consistent effect size. The significantly larger effect size of Solomon et al, 32 which reported a continuous measure, created heterogeneity that led to nonsignificant results. Similar limitations occurred in the in-person and group analyses in which Interian et al 19 and Holstad et al 26 also had larger effect sizes.…”
Section: Discussionmentioning
confidence: 96%
“…This was due to the variability in adherence measures that required further stratification of the (26,32,50), continuous (27); mixed MI: continuous (15,25); fidelity assessment: categorical (22,24,27,28,30,32), continuous (15, 15, 17-20, 22, 25, 27, 28, 33); no fidelity assessment: categorical (21,23,26,29), continuous (29); fidelity-based feedback: categorical (28,30,33), continuous (15,18,20,33,51); no fidelity-based feedback: categorical (21-24, 26, 27, 29, 32), continuous (19,22,25,27,29,34) Background of counselors: nurses: categorical (23,26,28,29), continuous (15,20,28,29); psychologist: continuous (17)(18)(19); pharmacists: categorical (32); master level: categorical (22,24), continuous ...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations